(untitled) (Bangladesh Agronomy Journal, 2025)
Effective weed management is always an important aspect in crop production. Of the all-possible weed control techniques including physical, chemical, mechanical, cultural and biological, use of chemical is always prioritized first to the farmers due to its’ quick response and effective weed control efficacy. However, selection of an optimized dose for each herbicide is crucial considering its’ effectivity and eco-toxicological aspect. An experiment was conducted at the research field of Agronomy Division, Gazipur during the Rabi season of 2013-2014 to find out the optimum rate of herbicide (MAGZIN 70 WG) to control weeds in brinjal field. Six treatments viz.: (i) MAGZIN 70 WG @ 750 mL ha−1 spraying at 15 DAS and 45 DAS, (ii) MAGZIN 70 WG @1000 mL ha−1 spraying at 15 DAS and 45 DAS, (iii) MAGZIN 70 WG @1250 mL ha−1spraying at 15 DAS and 45 DAS, (iv) MAGZIN 70 WG @ 1500 mL ha−1 spraying at 15 DAS and 45 DAS, (v) Two hand weedings at 30 and 60 DAS, (vi) No weeding (control) were used in the experiment. Among the weed species, Bathua (Chenopodium album), Durba (Cynodon dactylon), Anguli (Digitaria sanguinalis), Helencha (Jussiaea repens), Hatishur (Heliotropium indicum), Shama (Echinochloa crusgalli), Swetlomy (Gnaphalium japonicum), Mutha (Cyperus rotundus), Shaknote (Amaranthus viridis), Gaicha (Paspalum commersonii), Chapra (Eleusine indica), Bon Masur (Vicia sativa) were dominant in brinjal field. The results showed that the highest dry weight of weeds at 30 and 60 DAS were 12.24 gm m−2and 24.12 gm m−2, respectively found in control plot whereas the lowest with two hand weeding at 30 and 60 DAS. The maximum weed control efficiency (WCE) over control both at 30 and 60 DAS were 79.41 and 74.32%, respectively in treatment two hand weeding at 30 and 60 DAS. The highest number of fruits plant−1 (11.05), single fruit weight (86.48 g), fruit length (24.09 cm), yield (14.56 t ha−1) was found in two hand weeding and the lowest in no weeding (control). Though the WCE was highest in two hand weeding, but due to higher labor cost, the maximum benefit cost ratio (MBCR) (1.26) was highest in application of MAGZIN 70 WG@ 1500 mL ha−1 spraying at 15 and 45 DAS. As a system of mechanization of agriculture, the labor unavailability is a serious problem in Bangladesh. So, use of MAGZIN 70 WG@ 1500 mL ha−1 spraying at 15 DAS and 45 DAS may be economically viable. Bangladesh Agron. J. 2024, 27(2): 55-60